Pengaruh Layanan Bimbingan Kelompok Keterbukaan Diri (Self Disclousure) Peningkatan Kualitas Kegiatan Belajar terhadap Motivasi Berprestasi dalam Belajar - Sri Julianti Telaumbanua; Famahato Lase; Elizama Zebua; Hosianna Rodearni Damanik (Journal on Education, 2024)
Motivation for achievement in learning can be increased through various guidance and counseling services with appropriate and appropriate techniques. The aim of this research is to reveal the influence of group guidance services (X1), self-disclosure (X2), improving the quality of learning activities (X3) on achievement motivation in learning (Y), using the associative strategy quantitative method. The research location was students of SMA Negeri 1 Gunungsitoli, the research population was all students of class XI-IPS 2 and the sample was drawn using quota sampling as many as 33 people. The data collection instrument was a closed questionnaire which was distributed to a number of respondents. The data was analyzed analytically using multiple linear regression analysis, to answer the research hypothesis questions that had been asked. The results of the research concluded that self-disclosure group guidance services improved the quality of learning activities towards achievement motivation in learning, jointly and partially providing a very large influence and distribution on achievement motivation in learning. It is recommended that guidance and counseling teachers use group guidance services with various suitable and appropriate techniques.